Screening of multifunctional fruit carbon dots for fluorescent labeling and sensing in living immune cells and zebrafishes - Zhu, Weisheng (2023)
Nine kinds of carbon dots (CDs) were synthesized by using fruits with different varieties as carbon sources; meanwhile, the fluorescence characteristics, quantum yield, and response ability to different metal ions and free radicals were systematically studied. These CDs showed similar excitation and emission spectral ranges (λex ≈ 345 nm, λem ≈ 435 nm), but very different fluorescence quantum yield (QY), in which orange and cantaloupe CDs have the highest QY around 0.25 and green plum CDs showed the lowest quantum yield around 0.1. Interestingly, the fluorescence of all of these CDs can be significantly quenched by hydroxyl radical (•OH) and iron ion (Fe3+); however, these CDs showed very different response characteristics to other metal ions (e.g., Co2+, Ni2+, Cu2+, Ce3+, Mn2+, Ag+, and Fe2+). Through in-depth analysis, we found some interesting patterns of the influence of carbon sources on the fluorescence characteristics of CDs. Finally, by using white pitaya CDs as fluorescence probe, we realized sensing of Fe3+ and •OH with limits of detection (LOD) of 19.4 μM and 0.7 μM, respectively. Moreover, the CDs were also capable for sensitive detection in immune cells and even in zebrafishes. Our work can provide valuable guidance for the rational design of functional CDs for biological applications.